Modelagem numérico-computacional da coalescência de gotas e bolhas em escoamentos bifásicos turbulentos - Freitas, Ana Paula Moreira de (2023)
Gas-liquid and liquid-bubble flows are found in many industrial and academic applications, such as sprays, chemical reactions, and flotation. The modeling of the most relevant phenom- ena in these flows is essential to understand the behavior of the different phases and how this can influence the processes to which these flows are subjected. A phenomenon quite present in these flows is called coalescence, which, in short, consists of the agglomeration of bubble- bubble or drop-drop, forming bubbles or larger drops. Thus, the objective of this dissertation is the implementation and validation of a coalescence model in the MFSim computational code. To verify and validate this model, two case studies were used: one that consists of two clouds of droplets that collide with each other and the other that is a column of bubbles in a homoge- neous regime. The first case allows verifying the behavior of the algorithm for this simulation, verifying several coalescence factors and the output of these results. The bubble column, on the other hand, allows validating the amount of linear movement, comparing with data present in the literature, in addition to evaluating the coalescence in this type of flow. The results found for all two cases were satisfactory, and with that, it is concluded that using MFSim it is possi- ble to simulate gas-liquid and liquid-bubble flows, in which the phenomenon of coalescence is relevant.